Optimization and scale-up of α-amylase production by Aspergillus oryzae using solid-state fermentation of edible oil cakes - Balakrishnan, M. (BMC Biotechnol, 2021)
BACKGROUND: Amylases produced by fungi during solid-state fermentation are the most widely used commercial enzymes to meet the ever-increasing demands of the global enzyme market. The use of low-cost substrates to curtail the production cost and reuse solid wastes are seen as viable options for the commercial production of many enzymes. Applications of α-amylases in food, feed, and industrial sectors have increased over the years. Additionally, the demand for processed and ready-to-eat food has increased because of the rapid growth of food-processing industries in developing economies. These factors significantly contribute to the global enzyme market. It is estimated that by the end of 2024, the global α-amylase market would reach USD 320.1 million (Grand View Research Inc., 2016). We produced α-amylase using Aspergillus oryzae and low-cost substrates obtained from edible oil cake, such as groundnut oil cake (GOC), coconut oil cake (COC), sesame oil cake (SOC) by solid-state fermentation. We cultivated the fungus using these nutrient-rich substrates to produce the enzyme. The enzyme was extracted, partially purified, and tested for pH and temperature stability. The effect of pH, incubation period and temperature on α-amylase production using A. oryzae was optimized. Box–Behnken design (BBD) of response surface methodology (RSM) was used to optimize and determine the effects of all process parameters on α-amylase production. The overall cost economics of α-amylase production using a pilot-scale fermenter was also studied. RESULTS: The substrate optimization for α-amylase production by the Box–Behnken design of RSM showed GOC as the most suitable substrate for A. oryzae, as evident from its maximum α-amylase production of 9868.12 U/gds. Further optimization of process parameters showed that the initial moisture content of 64%, pH of 4.5, incubation period of 108 h, and temperature of 32.5 °C are optimum conditions for α-amylase production. The production increased by 11.4% (10,994.74 U/gds) by up-scaling and using optimized conditions in a pilot-scale fermenter. The partially purified α-amylase exhibited maximum stability at a pH of 6.0 and a temperature of 55 °C. The overall cost economic studies showed that the partially purified α-amylase could be produced at the rate of Rs. 622/L. CONCLUSIONS: The process parameters for enhanced α-amylase secretion were analyzed using 3D contour plots by RSM, which showed that contour lines were more oriented toward incubation temperature and pH, having a significant effect (p < 0.05) on the α-amylase activity. The optimized parameters were subsequently employed in a 600 L-pilot-scale fermenter for the α-amylase production. The substrates were rich in nutrients, and supplementation of nutrients was not required. Thus, we have suggested an economically viable process of α-amylase production using a pilot-scale fermenter.